2007
DOI: 10.1002/cmdc.200600263
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Antimalarial Compound Dioncophylline C Forms a Complex with Heme in Solution

Abstract: A structural model of the complex formed between the novel antimalarial compound dioncophylline C (DioC) and its presumed target ferriprotoporphyrin IX heme (FPIX) is presented. The complex structure was calculated with molecular dynamics (MD) simulations using intermolecular distance restraints between DioC and the iron center in FPIX, determined from NMR paramagnetic relaxation. Besides the spin state of the iron and longitudinal relaxation rates of hydrogen nuclei in DioC, the effective correlation time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…[27] Very recently, structure determination by NMR spectroscopy showed CQ sitting in a central position over the outermost porphyrin rings of a FPIX-CQ 4:2 complex. [28] Furthermore, CQ inhibits the glutathione-mediated and hydrogen peroxide-mediated destruction of FPIX. [24,29] Most researchers assume that the buildup of noncrystalline FPIX, either in its free form or as a FPIX-CQ complex, finally kills the parasite.…”
Section: Chloroquinementioning
confidence: 99%
“…[27] Very recently, structure determination by NMR spectroscopy showed CQ sitting in a central position over the outermost porphyrin rings of a FPIX-CQ 4:2 complex. [28] Furthermore, CQ inhibits the glutathione-mediated and hydrogen peroxide-mediated destruction of FPIX. [24,29] Most researchers assume that the buildup of noncrystalline FPIX, either in its free form or as a FPIX-CQ complex, finally kills the parasite.…”
Section: Chloroquinementioning
confidence: 99%
“…The spin state S is accessible using the "Evans method". A detailed description of the entire process can be found in [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…The first atomic resolution structures of FPIX in complex with several antimalarial drugs as determined by NMR were presented by De Dios and co-workers [7]. The technique was further refined in our group [8] to additionally include the determination of effective correlation times of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting work involving correlation times from paramagnetic relaxation, determined from measurements at three different magnetic fields, has shown that the antimalarial compound dioncophylline C binds with heme in solution in a chloroquine-like manner, indicating its mechanism of antimalarial activity and giving fundamental information for optimization of this type of drugs [44].…”
Section: Spin-lattice Relaxationmentioning
confidence: 99%